Surface modification of an intraocular lens material by plasma-assisted grafting with 2-hydroxyethyl methacrylate (HEMA), for controlled release of moxifloxacin - Vieira, Ana (2018)
Endophthalmitis, an inflammation of the eye due to perioperative infection, may occur after cataract surgery. Intraocular lenses (IOLs) loaded with an antibiotic have been proposed as an alternative to the conventional postoperative endophthalmitis prophylaxis, since the antibiotic is delivered directly to the target site. In this work, an IOL-based antibiotic releasing system was prepared from a copolymer used in the production of IOLs and a fluoroquinolone used in endophthalmitis prophylaxis (moxifloxacin, MFX). Argon plasma-assisted grafting with 2-hydroxyethyl methacrylate (HEMA) in the presence of MFX was the approach selected for surface modification, with MFX loaded both by entrapment in the grafted polyHEMA coating and by soaking. Surface and bulk properties were evaluated before and after surface modification and the MFX release profiles were obtained both in batch mode (sink conditions) and under hydrodynamic conditions, employing a purpose-built microfluidic cell, which simulated the hydrodynamic conditions around the eye lens. The effect of storage on the release profile of the best system was also assessed. The best system released MFX for ca. 15 days above the minimum inhibitory concentration for Staphylococcus aureus and Staphylococcus epidermidis. The released MFX showed antimicrobial activity against these bacteria and was non-cytotoxic against corneal endothelial cells.